Peningkatan Kemampuan Membaca dan Memahami Teks pada Siswa SMP Melalui Strategi Pertanyaan dan Jawaban (QAR) : Meningkatkan Reading Comprehension di Sekolah Menengah Pertama Melalui Strategi QAR - Afrizal Fikri Fathoni; Budiasih; Sujito; Zainal Arifin (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Reading comprehension represents a crucial aspect of learning English effectively, yet many junior high school students struggle to interpret and engage meaningfully with texts. Purpose: This study examines the impact of the Question Answer Relationships (QAR) strategy on enhancing students’ performance in reading comprehension. Method: This study employed a quantitative one-group pretest–posttest design involving 30 students from an Islamic Public Junior High School (JHS) in Karanganyar, selected through simple random sampling. Pre- and post-tests based on descriptive texts aligned with the national English curriculum were administered, and the data were analyzed using descriptive statistics and a paired-sample t-test to assess changes in students’ reading comprehension. Results and Discussion: The analysis showed that employing the QAR strategy resulted in a notable enhancement of students’ reading comprehension abilities. The average score improved from 22.67 on the pre-test to 32.53 on the post-test. Statistical results from the paired-sample t-test verified a significant improvement (t = –26.191, p < .001), indicating the effectiveness of the intervention. These results suggest that QAR supports students’ understanding of text by helping them differentiate between information derived directly from the text and knowledge constructed from prior understanding, thereby strengthening metacognitive engagement and filling the gap in strategies for fostering comprehension at the junior high level. Conclusions and Implications: The implementation of the QAR strategy provides a learning experience that guides students to think critically, understand the relationship between questions and the text, and gradually enhance their reading comprehension skills. QAR can serve as an innovative instructional approach for English teachers to foster students’ deeper understanding of reading comprehension.